Rebuke for the Ijtihad of the Prophet (Study of Q.S Al-Nisaâ€™ [4]: 34 as a Verse â€˜ItÄb) - Affani, Syukron (IAIN Pekalongan, 2021)
As a human being, the Prophet was involved humanly in various dynamics of life. The Prophet used ijtihad reasoning and subjective tendencies, which are of course relative, in responding to life's problems. As a messenger of Allah, the actions and words of the Prophet are decisions for Muslims except for revelation with other provisions from Allah such as with Q.S al-Nisa ' 4:34; one of the verses that presents a lot controversial discussion. The Prophet's decision to qiá¹£Äá¹£ a husband who committed violence against his wife, his passion is to provide justice and protection to women, but the decision was overturned by Q.S al-Nisa ' 4:34 which came down with other provisions as well as nuances of reprimand to the Prophet. The problem to be revealed in this paper is why Q.S al-Nisa ' 4:34 intervened in the Prophet's decision in responding to domestic violence. This research is a qualitative library research. The method of description is descriptive-analytical, which explains the basic construction of the Prophet's ijtihad and the significance of Q.S al-Nisa 4:34 to be analyzed using a historical-hermeneutical approach. The general conclusion from this paper is that Q.S al-Nisa' [4]: 34 places the issue of household and gender relations in the perspective of a social order that has been widely applied. The decision of the Prophet's qiá¹£Äá¹£ itself is not wrong but tark al-awlÄ (leaving a better thing) because it can actually increase the escalation of domestic conflicts in patriarchal society.